MANAJEMEN HUBUNGAN PELANGGAN PADA UMKM ARE SINGKONG BALADO - Hasan, Golan; Eddyanto, Dicky; Tan, Jordhan; Sherlyn, Sherlyn (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the application of customer relationship management (CRM) in MSMEs Are Singkong Balado. Are Sakkong Balado is an MSME engaged in the production and sale of balado cassava snacks. The research was conducted using a qualitative method through direct observation and interviews with business owners. The analysis is conducted using a CRM framework that includes customer identification, customer differentiation, interaction with customers, and service personalization. The results of the research show that Are Singkong Balado has implemented several aspects of CRM in running its business. Customer identification is done by segmenting customers based on frequency and number of purchases. Loyal customers are given special treatment such as discounts and service priority. Interaction with customers is done through social media and messaging apps. Service personalization is realized by offering products based on customer preferences. However, the implementation of CRM at Are Singkong Balado is still not optimal. There is no structured customer data recording system, making it difficult to analyze customer behavior and needs. The use of technology for CRM is also still minimal. Therefore, Are Singkong Balado needs to develop a more comprehensive and integrated CRM strategy by utilizing relevant technology. With a better CRM, Are Cassava Balado can increase customer loyalty, maintain business growth, and stay ahead of the competition.